Implementation of the electronic community health information system in rural East Shewa zone, Eastern Ethiopia: a CFIR-ERIC framework for facilitators, barriers and implementation strategies - Degaga, Serbesa Dereje; Yesuf, Solomon Shiferaw; Aweke, Girma Taye (Frontiers in Digital Health, 2025)
BackgroundThe Electronic Community Health Information System (eCHIS) is a key initiative of Ethiopian government to digitize the Health Extension Program and enhance community health services. Its effective implementation requires identifying key barriers and facilitators to inform tailored strategies. This study employed the Consolidated Framework for Implementation Research (CFIR) to explore implementation determinants and used the Expert Recommendations for Implementing Change (ERIC) to develop context-specific strategies aimed at strengthening eCHIS adoption and sustainability.MethodsAn exploratory case study design was employed in rural districts of East Shewa Zone, Eastern Ethiopia. Data were collected from November 5 to 25, 2024. A total of 24 face-to-face in-depth interviews were carried out with key informants across multiple sites. All interviews were audio-recorded, transcribed verbatim, and subsequently translated into English for analysis. Data were coded using Open code 4.03 software and thematically analyzed. Findings were interpreted using the CFIR–ERIC framework.ResultsWithin the Intervention Characteristics of CFIR domain, barriers included perceptions of eCHIS as an externally imposed system and the lack of interoperability with existing systems. Conversely, the comprehensive design of eCHIS, including integrated job aids, was recognized as a facilitating factor. In the Outer Setting domain, weak community engagement and the absence of clear implementation guidelines were cited as major barriers. For the Inner Setting domain, data synchronization challenges were highlighted as barriers, while the provision of tablets and accessories was identified as a facilitator. Under the Characteristics of Individuals domain, strong self-efficacy and a belief in eCHIS's positive impact on service delivery were noted as facilitators. Finally, in the Implementation Process domain, the lack of planning and leadership engagement was perceived as a barrier, whereas the availability of technical support and feedback mechanisms emerged as critical facilitators. Seven strategies to enhance implementation were developed such as Strengthening leadership engagement, developing clear guideline, fostering community engagement, creating system interoperability, establishing robust feedback systems, integrating health worker incentives program and enhancing technical support.ConclusionThe study offers key insights into the barriers, facilitators, and strategies of eCHIS implementation. Applying these strategies could strengthen implementation, enhance adoption, and promote long-term sustainability.